PENGARUH KESEHATAN DAN KESELAMATAN KERJA (K3) TERHADAP KINERJA KARYAWAN PABRIK KELAPA SAWIT DI PT. DSN - Mohamad Ali Widodo; Erna Rositah; Budi Winarni (Politeknik Pertanian Negeri Samarinda, 2021)
This research is based on the importance of applying occupational health and safety to employees of palm oil mills, It is worth noting that by providing awareness to factory employees about occupational health and safety will improve the performance of these employees.The purpose of this research is to know the characteristics of factory employees in the production section and the influence of occupational health and safety on the performance of employees of palm oil mills production parts.The time and place of this research was conducted on December 2 to December 21, 2020 and took place at PT. DSN and located in Muara Wahau District. The research method used is quantitative by using the dissemination of statement questionnaires with variables of health, safety, and employee performance. Researcher data processing techniques use validity tests, reliability tests, and multiple linear regression analysis through spss 22 applications.From the results of research activities that have been conducted by researchers obtained data that shows that there is a positive and significant influence between occupational health and safety variables to the performance variables of factory employees.